Toss the bouquet : [large type] three spring love stories - Herne, Ruth Logan; Matayo, Amy; Thompson, Janice A. (Thorndike Press large print Christian romance series., 2016)
All Dressed Up in Love: Tara walks into Elena's Bridal and finds her dream job -- and a man to match. But can their attraction take root amidst the demands of Bridezillas? In Tune with Love: April knows her job as maid of honor -- whatever the bride wants, she will have. Unless it involves Jack Vaughn. Never a Bridesmaid: Mari wants her sister's wedding to be perfect, but a poorly-chosen maid of honor may mean disaster.